POWER RELATIONS IN THE CONTEXT OF LITERACY IMPROVEMENT IN EAST JAVA, INDONESIA - Hamudy, Moh Ilham A; Rifki, M. Saidi (JWP (Jurnal Wacana Politik), 2025)
This study examines power relations in the context of literacy improvement in East Java Province. In addition to the persistent stagnation in TGM and IPLM scores, the Library and Archive Office (Dispusip) of East Java Province also faces unequal access to and varying quality of library services, which are crucial in improving literacy levels in East Java. These challenges are deeply intertwined with power relations, where leaders wield dominant influence over decision-making processes and policy implementation. This study employed a combination of descriptive and literature review methods, with data analysis conducted through a qualitative approach. It uncovered various factors and implications related to power relations within the Library and Archive Office (Dispusip) of East Java, particularly the hierarchical power structures and centralization. In this context, the Secretary of the Library Office (Sekdis) played a dominant role in shaping decision-making processes. The outcomes of centralized power encompassed power imbalances and internal conflicts within the Dispusip, including a noteworthy observation that numerous librarians launched programs without seeking approval from their leaders. Furthermore, the study highlights the librarians’ challenges in adapting to evolving demands, primarily stemming from limited human resource capabilities, which consequently lead to a decline in their performance. In response to these intricate challenges, this study underscores the importance of promoting open dialogues through participatory forums, implementing the principles of good governance, and empowering individuals by enhancing their skills and knowledge base.